2019
DOI: 10.1101/754390
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cdc42 promotes Bgs1 recruitment for septum synthesis and glucanase localization for cell separation during cytokinesis in fission yeast

Abstract: Cytokinesis in fission yeast involves actomyosin ring constriction concurrent to septum synthesis followed by septum digestion resulting in cell separation. A recent report indicates that endocytosis is required for septum synthesis and cell separation. The conserved GTPase Cdc42 is required for membrane trafficking and promotes endocytosis. Cdc42 is activated by Guanine nucleotide exchange factors (GEFs). Cdc42 GEFs have been shown to promote timely initiation of septum synthesis and proper septum morphology.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 27 publications
(36 reference statements)
1
20
0
Order By: Relevance
“…However, few proteins are known to regulate the localization of both classes of enzymes. Recently, Cdc42 GTPase was shown to promote recruitment of Bgs1 to the division site and be critical for proper localization of Eng1 and Agn1 (Onwubiko et al, 2020). Here we showed that Smi1 is important for division-site localization of both glucan synthases and glucanases, suggesting an interesting dual role of Smi1 in septum integrity.…”
Section: Roles Of Smi1 In Regulating Septum Integrity During Cytokinesismentioning
confidence: 55%
“…However, few proteins are known to regulate the localization of both classes of enzymes. Recently, Cdc42 GTPase was shown to promote recruitment of Bgs1 to the division site and be critical for proper localization of Eng1 and Agn1 (Onwubiko et al, 2020). Here we showed that Smi1 is important for division-site localization of both glucan synthases and glucanases, suggesting an interesting dual role of Smi1 in septum integrity.…”
Section: Roles Of Smi1 In Regulating Septum Integrity During Cytokinesismentioning
confidence: 55%
“…Previous reports have shown that membrane trafficking events are essential for successful cytokinesis 3,6,28 . Our findings illustrate the importance of spatiotemporally regulating membrane trafficking events during cytokinesis to properly coordinate actomyosin ring constriction, membrane furrow ingression, and septum synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, after completion of ring constriction and septum maturation, the primary layer of the septum is digested by the glucanases Eng1 and Agn1 to physically separate the daughter cells, completing division [11][12][13][14][15][16] . Cdc42 activity is necessary for the delivery of the primary septum synthase Bgs1 as well as the septum digesting glucanases Eng1 and Agn1 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported that the glucanases do not localize properly to the outer edge of the membrane barrier in a hypomorphic mutant of the small GTPase Cdc42 (Onwubiko et al, 2020). Cdc42 activity stops at the cell ends during mitosis and transitions to the division site during cytokinesis (Merla and Johnson, 2000;Rincon et al, 2007;Wei et al, 2016).…”
Section: Cdc42 Activation At Cell Ends Is Cell-cycle-dependentmentioning
confidence: 99%
“…The Rho GTPase Cdc42 is a major regulator of cell growth and polarity, and is highly conserved among eukaryotes (Etienne-Manneville, 2004;Johnson, 1999). Recently, we have shown that Cdc42 also plays a role in cytokinesis Onwubiko et al, 2020;Wei et al, 2016). Regulation of Cdc42 determines when and where polarization occurs (Das et al, 2012;Das et al, 2009;Etienne-Manneville, 2004;Howell et al, 2012).…”
Section: Introductionmentioning
confidence: 99%